Efficient White Polymer Light‐Emitting Diode (WPLED) Based on Single‐Component Eu3+–Tb3+‐Containing Metallopolymer. Issue 22 (23rd August 2019) - Fu, Guorui; Liu, Lin; Li, Wentao; He, Yani; Miao, Tiezheng; Lü, Xingqiang; He, Hongshan
Abstract: Despite the excellent physical properties of single‐component Eu 3+ –Tb 3+ ‐containing metallopolymers, the development of their flexible white polymer light‐emitting diodes (WPLEDs) for portable full‐color flat displays remains a formidable challenge. Herein, the WPLEDs from a metallopolymer Poly(NVK‐ co ‐2‐ co ‐7) are reported, in which [Eu(DBM)3 (4‐vp‐PBI)] (2 ) and [Tb(tba‐PMP)3 (4‐vp‐PBI)] (7 ) with different localized circumstances are grafted into poly( N ‐vinyl‐carbarzole) (PVK). In this design, both Dexter and Förster energy transfers occur, which endow a photoluminescent quantum yield up to 22.3% of the straightforward high‐quality white‐lights. Contributing from the stepwise alignment of frontier molecular orbitals of Poly(NVK‐ co ‐2‐ co ‐7) as the emitting layer in combination with CBP‐ and BCP‐assisted carrier‐transports, a reliable WPLED with the record‐renewed electroluminescent performance ( L Max = 388.0 cd m −2, ηc Max = 31.1 cd A −1, ηp Max = 15.0 lm W −1, ηEQE Max = 18.1%, and weak efficiency‐roll‐off) among previous organo‐Ln 3+ ‐based white organic light‐emitting diodes/WPLEDs is achieved. This finding renders a single‐component Eu 3+ –Tb 3+ ‐containing metallopolymers a potential new platform to cost‐effective flexible WPLEDs for practical applications. Abstract : Using the single‐component Eu 3+ –Tb 3+ ‐containing metallopolymer Poly(NVK‐ co ‐2‐ co ‐7) with the straightforward high‐quality white‐lights as the emitting layer, its reliable WPLED with stepwise alignments of both HOMO and LUMO levels affords the record‐renewed electroluminescent performance among previous organo‐Ln 3+ ‐based WOLEDs/WPLEDs.